利用亲水富集策略分析人血浆中N-糖基化蛋白及N-糖类型 = Analysis of N-glycosylated protein and N-glycans in human plasma by hydrophilic enrichment strategy - 马成 Ma, Cheng (2015)
蛋白质的N- 糖基化是最重要的翻译后修饰之一, 许多已知的血浆肿瘤诊断标志物及治疗靶标都是N- 糖基化 蛋白。 针对血浆的糖蛋白质组研究有利于发现新的蛋白标志物。然而，血浆蛋白质浓度分布的动态范围非常宽，且同一位点上的糖链存在微观不均一性，影响了血浆中糖蛋白的鉴定效率。本文利用亲水材料ZIC-HILIC制备亲 水富集柱分别对人血浆中的N- 糖链和N- 糖肽进行富集，并结合碱性反相色谱进行肽段的预分离和高准确度质谱 分析，最终在健康人的血浆中鉴定到了 ２９９ 个糖基化蛋白、６３７ 个糖基化位点，并识别出 ３１ 种不同的糖型。在这些 鉴定到的糖基化位点中，新发现有 １０７ 个 N- 糖基化位点(占总位点数的 １６.８％)。 本方法操作简单，可以有效富集N- 糖肽和 N- 糖，为在血浆中寻找糖蛋白和糖链生物标志物提供了可靠的手段。N-glycosylation of proteins is one of the most important post-translational modifications (PTM). Many diagnostic biomarkers and therapeutic targets are glycosylated proteins. However, it is still a big challenge to identify glycoproteins in human plasma, because of the high dynamic range and microheterogeneity of glycosylation. In this work, hydrophilic interaction liquid chromatography (HILIC) enrichment, high-pH reversed-phase prefractionation and high accurate mass spectrometry (MS) analysis were combined to profile the N-glycoproteins in human plasma. In total, 637 N-glycosites from 299 glycoproteins (protein groups) were identified. There were also 31 glycoforms recognized after HILIC enrichment and MS analysis. Among the results, 107 glycosylation sites (16.8%) are newly found. This study provided a simple and reliable strategy for exploring potential N-glycoprotein biomarkers from complicated biological systems.